Non-medical switch from the originator to biosimilar and between biosimilars of adalimumab in inflammatory bowel disease – a prospective, multicentre study. Issue 12 (December 2022) - Lontai, Livia; Gonczi, Lorant; Balogh, Fruzsina; Komlodi, Nora; Resal, Tamas; Farkas, Klaudia; Molnar, Tamas; Miheller, Pal; Golovics, Petra A.; Schafer, Eszter; Szamosi, Tamas; Ilias, Akos; et al.
Abstract: Introduction: Clinical data on the efficacy and safety of non-medical switch between adalimumab(ADA) biosimilars are limited. Aims: The aim of this study was to evaluate medium-term clinical efficacy, drug sustainability and safety comparing non-medical switches from the originator to biosimilar ADA, and between ADA biosimilars. Methods: 276 consecutive patients on maintenance ADA therapy ( n = 205 Crohn's disease, n = 71 ulcerative colitis) were included. Data on clinical efficacy, biomarkers and adverse events were collected at four time points: 8–12 weeks prior switch, at baseline/switch, 8–12 weeks and 20–24 weeks after switch. Drug survival was evaluated after a median 40(IQR:35–42) weeks follow-up. Results: A total 174 patients underwent a non-medical switch from the originator to a biosimilar, and 102 patients had a biosimilar-to-biosimilar switch. No significant difference was found in clinical remission rates at any time point in patients switching from originator to biosimilar(87.3%/88.5%/86.5%/85.7%) or biosimilar to biosimilar(74.5%/78.4%/85.3%/79.8%). Mean C-reactive protein levels remained unchanged in both cohorts( p = 0.856 and p = 0.525). Drug survival was similar between the two cohorts with a probability of 91.6%(SE: 2.2) and 87.0%(SE:3.4) to stay on drug after 40 weeks(log-rank:0.96; p = 0.327) . Five cases of injection related adverse events were reported. Conclusion: Clinical benefit was sustained following non-medical switch from originator to biosimilar, or between biosimilars in adalimumab treated IBD patients.